Investigating the effect of seed coating with micronutrient elements, regulators and growth stimulants on the characteristics of germination and growth of sugar beet seedlings of Cv. Shekoofa - Mahboobe Mohammadi; Mohammad Hassan Rashed Mohassel; Ehsan Neamatollahi (علوم و فناوری بذر ایران)
This experiment was designed to investigate the effect of seed coating with micronutrient elements, regulators and growth stimulants on the characteristics of germination and seedling establishment of sugar beet seeds, and in the form of a completely randomized design with four repetitions in the year 2020, in the Razavi Seed and Plant Institute was carried out under laboratory and greenhouse conditions. The treatments of this experiment were different combinations of micronutrient elements, regulators and growth stimulants which included 29 treatments along with a control treatment (without coating). The results showed that germination percentage, daily germination rate, germination rate coefficient, root and shoot length, root and shoot dry weight, and seedling root length index were significantly affected. Seed coating treatments were applied. In general, treatment 21, including macro elements + micro elements + humic acid + Gibberellic acid, with a germination percentage of 97%, seedling length index 13.87, allometric coefficient 0.2232, as the best treatment, increasing the mean You have a witness about the treatment. Also, among the different seed coating treatments, treatment 22, including microelements + humic acid + Gibberellic acid + kaolin, had the highest percentage of seedling establishment with 95%. Seed coating with micronutrients, humic acid and Gibberellic acid had the greatest effect on improving seedling growth and quality and germination percentage.